ULTRAHIGH-TEMPERATURE METAMORPHISM IN THE PALNI HILLS SOUTH INDIA: INSIGHTS FROM FELDSPAR THERMOMETRY AND PHASE EQUILIBRIA - Prakash D.; Mohan A.; Arima M. (My University, 2006)
The Southern Indian shield is a classic terrain that may be regarded as a model for Precambrian crustal evolution. The Palni Hills represent a portion of the granulite-facies terrain of the Madurai block. Determination of ultrahigh temperature (UHT) in granulites requires re-integration of anti-perthite, perthite, and mesoperthite to yield original hypersolvus feldspar compositions, which then yield peak metamorphic temperatures by feldspar solvus geothermometry. Backscattered electron images were used to calculate modal proportions of host and exsolved lamellae in feldspars. These data were combined with quantitative point chemical analyses of both host and lamellae to obtain re-integrated feldspar compositions, providing consistent ultrahigh temperatures in excess of 900°C. The feldspar compositions coexisting during closure of intercrystalline Al-Si exchange were calculated by reversing the K-Na exchange through shifts of Ab and Or contents of both feldspars at constant An contents until the equilibrium tie-line and the common isotherm on the ternary feldspar solvus were found. Besides, UHT metamorphic conditions were also obtained using the convergence method in exchange thermometers, suggesting peak metamorphism conditions at > 900°C at 9 kbar for the Palni granulites. Prevalence of UHT conditions in the many parts of the world could be useful in deducing Proterozoic tectonometamorphic processes along the deep crust-mantle interface. Copyright © 2006 by V. H. Winston & Son, Inc. All rights reserved.
Keywords: Proterozoic; Cambrian; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic::Cambrian; Палеозой::Кембрийская